Effectiveness of Project-Based Learning Models in Vocational Schools: A Study on Productive Subjects - Aurora Tjokro, Anita; Aris Ichwanto, Muhammad; Suwarno, Eko; Tze Kiong, Tee (Yayasan Lembaga Studi Makwa, 2023)
One of the lessons that can improve every student's skills is Project-Based Learning (PjBL). PjBL itself can help students acquire knowledge by solving real-world problems in project tasks. This learning phase can gradually increase students' motivation. At first, students will have difficulty with this, but over time they will gain experience to get used to solving different problems in each part of the project. Therefore, students' competence will continue to increase in the final phase as more and more of them put learning theory into practice. To determine to what extent the students' learning success increases through the use of PjBL in class, the use of joint project tasks in several subjects is examined. The study was conducted using Classroom Action Research (PTK) consisting of 2 cycles. The research location is at SMKN 1 Blitar with the research sample being type XII PPIB 1. The tools used are observation forms for quantitative data and interview forms for qualitative data. Observation of student learning activities is carried out during the teaching and learning process. The general project task topics covered are Software Application and Building Interior Design (APLPIG), Construction Cost Estimation (EBK), and Building Utility Construction (KUG). The observed results show that in cycle 1 the average value of student learning activities is 69.19%, while in cycle 2 the average value of student learning activities is 78. 82%. Based on the results of hypothesis testing in each subject, it was found that the average score of each student increased from cycle 1 to cycle 2. In addition, through observing 7 types of learning activities, we also found that each student increased in each subject. type of learning activities in PTK. In summary, learning activities increased when PjBL was implemented Abstrak Salah satu jenis pembelajaran yang dapat meningkatkan kemampuan individu setiap siswa adalah pembelajaran berbasis proyek (PjBL). PjBL sendiri dapat membantu siswa memperoleh pengetahuan dengan memecahkan masalah kehidupan nyata dalam proyek. Fase pembelajaran ini memungkinkan motivasi siswa berkembang secara perlahan. Pada awalnya siswa akan mengalami kesulitan dalam mengerjakan, namun seiring berjalannya waktu, mereka akan memperoleh pengalaman dan terbiasa memecahkan masalah yang berbeda-beda di setiap bagian proyek. Pada tahap akhir keterampilan siswa akan terus meningkat karena pembelajaran teori banyak dipraktikkan. Penerapan proyek gabungan pada beberapa mata pelajaran akan diteliti untuk mengetahui sejauh mana peningkatan aktivitas belajar siswa ketika penerapan PjBL di kelas. Penelitian dilakukan dengan menggunakan Penelitian Tindakan Kelas (PTK) yang terdiri dari 2 siklus. Lokasi penelitian di SMKN 1 Blitar, sampel penelitiannya adalah tipe XII PPIB 1. Alat yang digunakan adalah lembar observasi sebagai data kuantitatif dan formulir wawancara sebagai data kualitatif. Observasi terhadap aktivitas belajar siswa dilakukan pada saat proses belajar mengajar. Sedangkan mata pelajaran yang ditugaskan pada proyek gabungan adalah aplikasi perangkat lunak dan desain interior (APLPIG), estimasi konstruksi (EBK), dan konstruksi utilitas (KUG). Hasil observasi menunjukkan bahwa pada siklus 1 nilai rata-rata aktivitas belajar siswa sebesar 69,19%, sedangkan pada siklus 2 nilai rata-rata aktivitas belajar siswa sebesar 78,82%. Berdasarkan hasil uji hipotesis pada setiap mata pelajaran diketahui bahwa rata-rata skor mengalami peningkatan dari siklus 1 ke siklus 2. Selanjutnya melalui pengamatan terhadap 7 jenis kegiatan pembelajaran juga terlihat bahwa setiap siswa mengalami peningkatan pada setiap jenis kegiatan pembelajaran. aktivitas belajar. kegiatan pembelajaran di PTK hari ini. Kesimpulannya, terjadi peningkatan aktivitas pembelajaran selama pelaksanaan PjBL.